﻿Clinical course and outcome of rheumatoid arthritis-related usual interstitial pneumonia - Song, J-W.; Lee, H.-K.; Lee, C.K.; Chae, E.J.; Jang, S.J.; Colby, T.V.; Kim, D.S. (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2013)
Background: Although the prognosis of interstitial pneumonia in connective tissue disorders is better than that of idiopathic pulmonary fibrosis (IPF), the prognosis of rheumatoid arthritis (RA) related usual interstitial pneumonia (UIP) is controversial. Objectives: To determine prognosis, clinical course and prognostic factors of the patients with RA-UIP and compare them to IPF. Design: Retrospective review of 84 patients with RA-UIP (biopsy-proven: 30) from two tertiary referral centers. Results: The median follow-up period was 33 months. One half of the patients were stable, one third progressed, 17% had acute exacerbation and 6% improved. TLC % predicted was the only significant predictor for the stable group. Among non-AEx patients, 41% was treated due to poor initial lung function or progression of the disease and one half of them improved or had stable lung function. Despite of worse initial lung function, the survival of treated group was similar to untreated group. Age, FVC and change in DLco during 6 months were significant predictors for mortality. The prognosis of RA-UIP was significantly better than that of IPF matched with age, sex, smoking and baseline lung function (median survival, 53 vs. 41 months respectively, p = 0.015). Conclusions: In spite of variable clinical course of RA-UIP, overall prognosis of RA-UIP was significantly better compared to IPF. Our data supported the treatment of the patients with significant functional impairments or progression.